(untitled) (Journal of the College of Basic Education, 2026)
Ancient Arabic musical references and manuscripts, as documented in the following divine books, confirm that singing and dancing have been a part of life in all civilizations since ancient times. This has also been confirmed by modern research. Arabs are the first to develop the theory of polyphony in their music, as found in the manuscripts of the philosopher Al-Kindi, who was the first to discuss polyphony in his book (A Treatise on Melodies and Maqamat). Accordingly, Iraqi music reflects its influence from many ancient and Islamic civilizations, which has led to a great diversity in the styles and techniques used in the structure of musical harmony. Iraqi music is characterized by a diversity and multiplicity of technical methods, influenced by various civilizations and cultures throughout the ages, which has been reflected in the structure of its harmonic harmony in general, and Iraqi music in particular. Accordingly, the research comprises four chapters, as follows: The first chapter addressed the research problem, which centered around the following question: "What is the structure of harmonic harmony in Iraqi maqam compositions as a model?" The importance of the research was evident in its study of "the structure of musical harmony in Iraqi maqam compositions." The research objective was to "reveal and identify the structure of musical harmony in Iraqi maqam according to horizontal and vertical harmony." As for the research boundaries, the temporal boundaries were limited to the year 2003, the spatial boundary was the city of Baghdad, and the thematic boundary was "Iraqi maqam music." The second chapter dealt with the theoretical framework. The first chapter included "The concept of Iraqi musical harmony and harmony," while the second chapter included "The importance of form in composing the Iraqi melodic structure." The third chapter dealt with the research procedures and sample analysis, and the fourth chapter dealt with the results and conclusions, followed by a list of sources.